2013
DOI: 10.5194/acp-13-9183-2013
|View full text |Cite
|
Sign up to set email alerts
|

A global model study of the impact of land-use change in Borneo on atmospheric composition

Abstract: In this study, a high resolution version of the Cambridge p-TOMCAT chemical transport model is used, along with measurement data from the 2008 NERC-funded Oxidant and Particle Photochemical Processes (OP3) project, to examine the potential impact of the expansion of oil palm in Borneo on atmospheric composition. Several model emission scenarios are run for the OP3 measurement period, incorporating emissions from both global datasets and local flux measurements. Using the OP3 observed isoprene fluxes and OH rec… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
46
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(48 citation statements)
references
References 55 publications
0
46
2
Order By: Relevance
“…Figure 10 shows that OH in CheT2 is indeed higher than in CheT over the main isoprene emitting regions, with maximum increases of approximately 50 %. Warwick et al (2013) also calculated that including the Peeters mechanism in UM-UKCA gave higher OH, improving agreement between modelled and measured values.…”
Section: Atmosmentioning
confidence: 99%
See 1 more Smart Citation
“…Figure 10 shows that OH in CheT2 is indeed higher than in CheT over the main isoprene emitting regions, with maximum increases of approximately 50 %. Warwick et al (2013) also calculated that including the Peeters mechanism in UM-UKCA gave higher OH, improving agreement between modelled and measured values.…”
Section: Atmosmentioning
confidence: 99%
“…Proposals have been put forward for missing mechanistic pathways, e.g. peroxy radical isomerisation (Peeters et al, 2009), and epoxide formation (Paulot et al, 2009) which to some extent reconcile these discrepancies (Archibald et al, 2010a;Warwick et al, 2013;Fuchs et al, 2013). It has also been demonstrated that positive biases in the measurement of HO 2 (Fuchs et al, 2011) and OH (Mao et al, 2012) cannot be ruled out in some of those field campaigns listed above.…”
mentioning
confidence: 99%
“…We do not attempt to model the detailed growth, harvesting, and senescence history of the plantation (Fan et al, 2015). Previous studies (Ashworth et al, 2012, andWarwick et al, 2013) did not explicitly simulate the concomitant changes to deposition due to oil palm expansion. They instead performed short sensitivity studies wherein Warwick et al (2013) doubled the modeled deposition velocities, and Ashworth et al (2012) scaled modeled deposition parameters (roughness length and LAI) by observed canopy height and biomass density.…”
Section: Description Of Sea Land Usementioning
confidence: 99%
“…The basal isoprene emission factor of oil palm is set to the basal rate of 7.8 mg m −2 h −1 measured during OP3 ; this basal emission factor is modulated online by local meteorology and phenology to estimate emissions. Previous studies scaled modeled emissions of broadleaf evergreen trees (Ashworth et al, 2012), or kept these emissions fixed to the measured rate during OP3 (Warwick et al, 2013). The basal isoprene emission factor of the native forests (considered to be broadleaf evergreen tropical trees) is reduced to 1.6 mg m −2 h −1 to match the OP3 measurements , which is a factor of 4 lower than the emission factors for broadleaf evergreen tropical trees within MEGANv2.1, and consistent with the rainforests of Southeast Asia emitting less isoprene than South American and African rainforests.…”
Section: Description Of Sea Land Usementioning
confidence: 99%
See 1 more Smart Citation